Time to go wild: How to conceptualize and measure process dynamics in real teams with high-resolution - Klonek, Florian; Gerpott, F.H.; Lehmann-Willenbrock, N.; Parker, Sharon (SAGE PUBLICATIONS INC, 2019)
Team processes are interdependent activities among team members that transform inputs into outputs, vary over time, and are critical for team effectiveness. Understanding the temporal dynamics of team processes and related team phenomena with a high-resolution lens (i.e., methods with high sampling rates) is particularly challenging when going “into the wild” (i.e., studying teams operating in their full situated context). We review quantitative field studies using high-resolution methods (e.g., video, chat/text data, archival, wearables) and map out the various temporal lenses for studying team dynamics. We synthesize these different lenses and present an integrated temporal framework that is of help in theorizing about team dynamics. We also provide readers with a “how to” guide that summarizes four essential steps along with analytical methods (e.g., sequential and pattern analyses, mixed-methods research, abductive reasoning) that are applicable to the broad scope of high-resolution methods.